Mapping men and empire a geography of adventure - Phillips, Richard (Routledge, 1997)
But beneath the map-like realism of adventure stories, there is an undercurrent of ambivalence. Adventure's geography is more fragile and also more fluid than it first appears. While adventure stories map, they also unmap geographies and identities, destabilising and sometimes recasting them. The ambivalent geography and politics of adventure are illustrated in late-Victorian and Edwardian girls' stories, in which boundaries between masculinity and femininity are blurred, and in contemporaneous stories by Jules Verne, which can be read as anarchist adventures